Herbal formula YGJDSJ inhibits anchorage-independent growth and induces anoikis in hepatocellular carcinoma Bel-7402 cells - Bing Hu; Tong Zhang; Hong-Mei An; Jia-Lu Zheng; Xia Yan; Xiao-Wei Huang (BMC, 2018)
Abstract Background Based on clinical medications and related studies, we established a Yang-Gan Jie-Du Sang-Jie (YGJDSJ) herbal formula for hepatocarcinoma treatment. In present study, we evaluated the anti-cancer potential of YGJDSJ on suspension-grown human hepatocellular carcinoma Bel-7402 cells. Methods Bel-7402 cells were cultured in poly(2-hydroxyethyl methacrylate) (poly-HEMA) coated plates and treated with YGJDSJ. Anchorage-independent cell growth was detected by cell Counting Kit-8 (CCK-8) assay and soft agar colony formation assay. Anoikis was detected by ethdium homodimer-1 (EthD-1) staining and flow cytometry analysis. Caspases activities were detected by the cleavage of chromogenic substrate. Reactive oxygen species (ROS) was detected by 2',7'-dichlorofluorescin diacetate (DCFH-DA) staining. Protein expression and phosphorylation was identified by western blot. Protein expression was knocked-down by siRNA. Results YGJDSJ inhibited the proliferation of Bel-7402 cells in poly-HEMA coated plates and anchorage-independent growth of Bel-7402 cells in soft agar. YGJDSJ also induced anoikis in Bel-7402 cells as indicated by EthD-1 staining and flow cytometry analysis. YGJDSJ activated caspase-3, − 8, and − 9 in suspension-grown Bel-7402 cells. The pan-caspase inhibitor Z-VAD-FMK significantly abrogated the effects of YGJDSJ on anoikis in suspension-grown Bel-7402 cells. In addition, YGJDSJ increased ROS in suspension-grown Bel-7402 cells. The ROS scavenger N-acetyl-L-cysteine (NAC) partially attenuated YGJDSJ-induced activation of caspase-3, − 8 and − 9 and anoikis in suspension-grown Bel-7402 cells. Furthermore, YGJDSJ inhibited expression and phosphorylation of protein tyrosine kinase 2 (PTK2) in suspension-grown Bel-7402 cells. Over-expression of PTK2 significantly abrogated YGJDSJ induced anoikis. Conclusions YGJDSJ inhibits anchorage-independent growth and induce caspase-mediated anoikis in Bel-7402 cells, and may relate to ROS generation and PTK2 downregulation.